Altruistic (Costly) Punishment as Motivation for Vindictive Rape - R. Karl Hanson (Sexual Offending, 2020)
This paper presents a model of vindictive rape based on common mechanisms for maintaining cooperation among humans, namely altruistic (or costly) punishment, sex role expectations, and retributive (“eye for an eye”) justice. Vindictive rapes are characterized by high level of victim harm without explicit sadistic sexual interests. They are also distinguished from angry, reactive sexual aggression in response to personal insult or threats. In this model, vindictive rape is considered a form of retributive justice in which the perpetrator punishes the female victim for perceived transgressions against sexual norms. None of the specific psychological mechanisms are intrinsically problematic. Nevertheless, individuals who have committed vindictive rapes would still be expected to have risk-relevant schema worthy of interventions. For such individuals, the primary treatment targets would be loosening rigid sexual norm expectations for women, increasing confidence in conventional methods of maintaining social order, and decreasing willingness to hurt others at the cost of hurting oneself. A 15-item Vindictive Rape Attitude Questionnaire is presented in order to facilitate further research on the topic.